Empowering Women Through Women's Organizations in Realizing Family Welfare (Edukasi, 2022)
This research aims to find women's organizations as a strategy for women's empowerment in realizing family welfare. This study used descriptive methods with a survey approach to get information on women's conditions and women's organizations as a strategy for women's empowerment. The selected respondents were village heads and Kalongan village women who actively participated in women's activities. Data collection techniques use interviews, observations, and documents. Data validity uses source triangulation techniques and methods—research data analysis using interactive models. The findings of this study are known that the condition of empowerment of Kalongan village women is considered not fully optimal. This is due to the low understanding of women's abilities as an important component of the family so many stereotypes arise in women that their rights and positions are only limited to male servants in the family. This patriarchal culture is a legacy of ancient life is still widely felt by women in Kalongan Village, especially in Bulu and Gondoriyo Hamlets, almost 63% of the community is still thick with religious nuances so many family heads limit the direction of women's movement to contribute to the public. The emergence of this stereotype makes married women depend entirely on their husbands, especially in economic problems that only rely on the husband's income to make women or wives helpless without the presence of a husband figure.